Herpes Simplex Virus Type 1 is the Leading Cause of Genital Herpes in New Brunswick - Richard Garceau; Danielle Leblanc; Louise Thibault; Gabriel Girouard; Manon Mallet (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Little is known about the role of herpes simplex virus (HSV) type 1 (HSV1) in the epidemiology of genital herpes in Canada. Data on herpes viral cultures for two consecutive years obtained from L’Hôpital Dr GL Dumont, which performs all the viral culture testing in New Brunswick, were reviewed. It was hypothesized that HSV1 was the main cause of genital herpes in New Brunswick.